Er3+-Yb3+/Er3+-Yb3+-Li+/Er3+-Yb3+-Zn2+:Gd2O3 nanophosphors for efficient frequency upconverter and temperature sensing applications. (October 2018) - Ranjan, Sushil Kumar; Mondal, Manisha; Rai, Vineet Kumar
Graphical abstract: Highlights: The Er 3+ -Yb 3+ :Gd2 O3 nanophosphors infer the enhancement in UC emission intensity via incorporation of Li + and Zn 2+ ions. The average particles size of the developed nanophosphors is found to be lie in nanometer range by XRD and TEM analysis. The maximum sensitivity ∼ 0.0116 K −1 has been reported in the Er 3+ -Yb 3+ -Zn 2+ :Gd2 O3 nanophosphors. The colour coordinate for the developed Er 3+ -Yb 3+ -Zn 2+ :Gd2 O3 nanophosphors lie in the greenish yellow colour region. Abstract: Er 3+ /Yb 3+ /Li + /Zn 2+ :Gd2 O3 nanophosphors synthesized via combustion synthesis method have been structurally and optically characterized. The average particles size of the developed nanophosphors has been found to be ∼ 25 nm by Transmission Electron Microscopy (TEM) analysis which is in good agreement with the X-rays Diffraction (XRD) results. The significant enhancement in upconversion (UC) emission intensity for green (∼ 20 and 70 times) and red (∼ 7 and 20 times) band have been observed after codoping with Li + and Zn 2+ ions respectively in Er 3+ -Yb 3+ :Gd2 O3 system. The temperature sensing capability of the optimized nanophosphors has been studied corresponding to two thermally coupled 2 H11/2 and 4 S3/2 levels of the Er 3+ ions. The sensitivity ∼ 0.0096 K -1, 0.00109 K -1 and 0.0116 K -1 have been reported in the Er 3+ -Yb 3+ :Gd2 O3, Er 3+ -Yb 3+ - Li + :Gd2 O3 and Er 3+ -Yb 3+ - Zn 2+ :Gd2 O3 nanophosphors respectively. The photometric characterizations of the developed nanophosphors have also been reported.